2006
DOI: 10.2307/3491251
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Predator and Prey Armament: Geographic Clines in Phenotypic Interface and Natural Selection

Abstract: The escalation of defensive/offensive arms is ubiquitous in prey-predator evolutionary interactions. However, there may be a geographically varying imbalance in the armaments of participating species that affects the outcome of local interactions. In a system involving the Japanese camellia (Camellia japonica) and its obligate seed predator, the camellia weevil (Curculio camelliae), we investigated the geographic variation in physical defensive/offensive traits and that in natural selection on the plant's defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(120 citation statements)
references
References 0 publications
3
117
0
Order By: Relevance
“…This suggests that a transcontinental comparison of the PA tolerance of snowshoe hares from regions home to birches with PA concentrations ranging from high to low is warranted, especially given the unprecedented spatial scale at which these terrestrial mosaics could operate relative to other previously documented consumer-resource mosaics (e.g., Thompson 2005;Thompson and Fernandez 2006;Toju and Sota 2006;Siepielski and Benkman 2007;Toju 2008). The comparison would be a transcontinental test of Thompson's (2005) geographic mosaic of coevolution hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that a transcontinental comparison of the PA tolerance of snowshoe hares from regions home to birches with PA concentrations ranging from high to low is warranted, especially given the unprecedented spatial scale at which these terrestrial mosaics could operate relative to other previously documented consumer-resource mosaics (e.g., Thompson 2005;Thompson and Fernandez 2006;Toju and Sota 2006;Siepielski and Benkman 2007;Toju 2008). The comparison would be a transcontinental test of Thompson's (2005) geographic mosaic of coevolution hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…Studies on the camelia weevil (C. cameliae) have shown that differences in rostrum length among populations are correlated with seed coat thickness (Toju and Sota 2006b). The plant and the insect are involved in a coevolutionary race in which thick seed coats promote the development of longer rostrums and vice versa (Toju and Sota 2006b). The pressure on rostrum length is strong, as evident from the disproportionally enlarged rostrum relative to body size in populations feeding on seeds with thick seed coats (Toju and Sota 2006a).…”
Section: Introductionmentioning
confidence: 98%
“…Most species are seed parasites and their main host plants are oaks, chestnuts, hazelnut trees and camelias (Hughes and Vogler 2004b). They exhibit long legs and a vastly extended rostrum that measures up to three times their body length, particularly in the females (Hughes and Vogler 2004a;Toju and Sota 2006b). The mandibles at the terminus of the rostrum are used to drill an oviposition hole by slowly chewing a narrow opening into the thick coating of the growing seed (Desouhant et al 2000;Muñoz 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view on coevolution has led to clear, testable predictions, and indeed these are taken up by an expanding range of scientists, who experimentally test these predictions in a variety of systems (e.g. Thompson 1999aThompson , b, 2009aBurdon and Thrall 1999;Lively 1999;Brodie et al 2002;Benkman et al 2003;Neuhauser et al 2003;Zangerl and Berenbaum 2003;Toju and Sota 2006). One of the central challenges is to explain the observed geographical distribution of alleles at adaptive loci in terms of selection (stabilizing, directional, disruptive or balancing) versus migration and genetic drift.…”
Section: Introductionmentioning
confidence: 94%